2022
DOI: 10.3389/fbioe.2022.1061855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of condylar chondrocyte exosomes on condylar cartilage osteogenesis in rats under tensile stress

Abstract: Background: Functional orthoses are commonly used to treat skeletal Class II malocclusion, but the specific mechanism through which they do this has been a challenging topic in orthodontics. In the present study, we aimed to explore the effect of tensile stress on the osteogenic differentiation of condylar chondrocytes from an exosomal perspective.Methods: We cultured rat condylar chondrocytes under resting and tensile stress conditions and subsequently extracted cellular exosomes from them. We then screened m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…found that MSC‐Exos enhanced s‐GAG synthesis impeded by IL‐1β and suppressed IL‐1β‐induced nitric oxide and MMP13 production. Shi et al 110 . found that Runx2 and Sox9 expression levels were considerably greater in the Force‐Exo group, suggesting that exosomes produced in cells cultured under tensile stress may find use in the treatment of OA.…”
Section: Resultsmentioning
confidence: 99%
“…found that MSC‐Exos enhanced s‐GAG synthesis impeded by IL‐1β and suppressed IL‐1β‐induced nitric oxide and MMP13 production. Shi et al 110 . found that Runx2 and Sox9 expression levels were considerably greater in the Force‐Exo group, suggesting that exosomes produced in cells cultured under tensile stress may find use in the treatment of OA.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, lncRNAs and circRNAs can participate in regulating transcription and translation processes directly by performing functions such as protein scaffolding, regulatory splicing, and loop-roll translation, or indirectly regulating signaling pathways by influencing other RNAs as miRNA sponges, thus participating in regulating tumorigenesis and development (10)(11)(12). ncRNAs are widely found in exosomes (13)(14)(15). In addition, miRNAs do not circulate in the body in a free state; they generally bind to AGO2 or lipoproteins or are encapsulated by vesicles such as exosomes before entering the circulation (as shown in Figure 1) (5).…”
Section: Introductionmentioning
confidence: 99%